"Climate tariffs" and the credibility of the EU climate and energy package: International climate policy and carbon leakage - Susanne Dröge (Stiftung Wissenschaft und Politik (SWP), 2008)
The French president Nicolas Sarkozy has repeatedly advocated strengthening the European climate and energy package by imposing tariffs on imports from world regions without an ambitious climate policy. Yet for a number of reasons, it remains ambiguous how trade-related policy instruments could contribute to the EU's climate strategy. Moreover, the EU faces the challenge of carbon leakage - the migration of emissions from the territory of the EU into non-EU regions through relocation of production and investment. This issue could come to the fore as the EU price on carbon emissions will increase following the current revision of the EU emissions trading scheme for the period after 2012. If the EU's climate policy should become a credible contribution to global carbon emissions reductions, the key issue is to deliver reductions within the EU territory. In order to reduce the relocation effects, carbon cost adjustments at the EU borders could in fact be applied to a small number of leakage-prone industries. At present, however, all attempts to bring this forward at the international level are being perceived by emerging economies as a threat. This in turn places at risk both the international negotiations on the future UN climate regime and the Doha Round negotiations on world trade
Keywords: 320